Biomimetic Futures: Life, Death, and the Enclosure of a More-Than-Human Intellect - Johnson, Elizabeth R.; Goldstein, Jesse (Annals of the Association of American Geographers, 2015)
The growing field of biomimicry promises to supplant modern industry's energy-intensive models of engineering with a mode of production more sensitively attuned to nonhuman life and matter. This article considers the revolutionary potentials created by biomimicry's more-than-human collectives and their limitations. Although biomimicry gestures toward a radical reontologization of and repoliticization of production, we argue that it remains subject to entrenched onto-political habits of social relations still dominated by capitalism and made part of a "terra economica" in which all is potentially put to profitable use and otherwise left to waste. With reference to Marx's notions of general industriousness and the general intellect, we find that this universalizing tendency renders myriad biological capacities and ways of knowing invisible. Drawing a comparison with the reworkings of life and knowledge explored in Shiebinger's work on nineteenth-century abortifacients, we show how biomimicry's more recent ontological remakings reproduce some forms of knowledge-and life-at the expense of others. Reflecting on biomimicry's inadvertent erasure of nonindustrial ways of knowing, we advance the notion of a pluripotent intellect as a framework that seeks to take responsibility for the cocuration of forms of life and forms of knowledge. We turn to Jackson's Land Institute as a grounded alternative for constructing more-than-human techno-social collaboratives.